SLIM'S STRUGGLE TO DEFEND HERSELF AT NICHOLAS KAZAN'S ENOUGH MOVIE (2002): A FEMINIST APPROACH - PRASETYOWATI, EKA DEWI (2011)
This study is aimed to show the against gender discrimination in Enough. movie by using feminist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the feminist approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Enough movie directed by Nicholas Kazan released in 2002. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other and form unity to be good quality of a movie. Second, based on the feminist analysis, Nicholas Kazan represents the form of gender discrimination. The character of Slim struggles for quality in position, role, right and participation.